Adalberto Tejeda and the Third Phase of the Anticlerical Conflict in Twentieth Century Mexico - Williman, John B. (A journal of church and state, 1973)
John B. Williman; Adalberto Tejeda and the Third Phase of the Anticlerical Conflict in Twentieth Century Mexico, Journal of Church and State, Volume 15, Issue 3